Exposure to metal mixtures in relation to blood pressure among children 5–7 years old: An observational study in Bangladesh. Issue 2 (11th April 2021) - Shih, Yu-Hsuan; Howe, Caitlin G.; Scannell Bryan, Molly; Shahriar, Mohammad; Kibriya, Muhammad G.; Jasmine, Farzana; Sarwar, Golam; Graziano, Joseph H.; Persky, Victoria W.; Jackson, Brian; Ahsan, Habibul; Farzan, Shohreh F.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Hypertension in later life, a significant risk factor for cardiovascular disease, has been linked to elevated blood pressure in early life. Exposure to metals may influence childhood blood pressure; however, previous research is limited and has mainly focused on evaluating the toxicity of single metal exposures. This study evaluates the associations between exposure to metal mixtures and blood pressure among Bangladeshi children age 5–7 years. Methods: We investigated the associations of 17 toenail metal concentrations with blood pressure using linear regression models. Principal component analysis (PCA), weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) were conducted as secondary analyses. Results: Associations were observed for selenium with diastolic blood pressure (per doubling of exposure β = 2.91, 95% confidence interval [CI] = 1.08, 4.75), molybdenum with systolic (β = 0.33, 95% CI = 0.05, 0.61) and diastolic blood pressure (β = 0.39, 95% CI = 0.12, 0.66), tin with systolic blood pressure (β = –0.33, 95% CI = –0.60, –0.06), and mercury with systolic (β = –0.83, 95% CI = –1.49, –0.17) and diastolic blood pressure (β = –0.89, 95% CI = –1.53, –0.26). Chromium was associated with diastolic blood pressure among boys only (β = 1.10, 95% CI = 0.28, 1.92, P for interaction = 0.02), and copper was associated with diastolic blood pressure among girls only (β = –1.97, 95% CI = –3.63, –0.32, P for interaction = 0.01). These findings were largely robust to the secondary analyses that utilized mixture modeling approaches (PCA, WQS, and BKMR). Conclusions: Future prospective studies are needed to investigate further the impact of early life exposure to metal mixtures on children's blood pressure trajectories and cardiovascular disease risk later in life.